Redeeming Gender Narratives of the Naga Community in Northeast India - Hungyo, N.N. (University of jaffna, 2024)
In this paper, I question the lack of discussion or silence surrounding toxic masculinity and submissive femininity in the Naga context. I argue for the need to challenge the presence of toxic gender norms that have created an environment of gender inequality, leading to an increase in domestic violence, abuse, disrespect for women, and denial of leadership roles in religious settings - and also offer insights on doing public theology as I argue for the need to redeem the gender narratives of the Naga community. I will use intersectionality as the methodology to identify how gender, patriarchal ideologies, culture, and religion intersect and contribute to these norms. Patriarchal culture and conservative religious doctrines have contributed to the development of toxic masculinity trends in men and submissive feminine traits among women in the Naga context. The Christian biblical depiction of God as a Father is used to support the claim that God is man and that men bear the image of God. The violent image of God in the Bible is also used to justify the violence of men, stating that such behaviour is necessary to be considered masculine. Although this may be the case, there is a scarcity of research on toxic masculinity and femininity in the Naga context. Many scholars support the current gender roles and argue that Naga women enjoy greater privileges than women in other parts of India due to the casteless and classless social system. The reality, however, is far from the truth. Women who vie for leadership positions, engage in public spaces, advocate inclusive reforms, and oppose toxic patriarchal practices often face public shame and social ostracism.
Keywords: Toxic masculinity; Gendering in naga community; Intersectional research